A dual-site doped iron-based phosphate composite material and its preparation method and application
By doping and carbon coverage of sodium -phosphate sodium phosphate material, the electronic conductivity of the material is low, the working voltage is not high, and the crystal structure is unstable, and the structural stability and cycle performance of the material are realized Improvement has significantly improved its electrochemical performance.
Patent Information
- Application Number
- CN202311732712.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-12-15
AI Technical Summary
The existing sodium ferric pyrophosphate materials have low inherent electron conductivity, low working voltage and unstable crystal structure, which affect their rate performance and cycle stability, hinder their electrochemical performance and practical application.
By double-site doping of the sodium site and iron site of the sodium iron pyrophosphate material, specific elements Zr, Cu, Mg, Sn, Mn, and Co are used to dope the A site, and Li and K are doped into the A site. B site, and carbon coating is performed on the basis of doping to form a dual-site doped iron-based phosphate composite material.
This method effectively improves the structural stability and cycle performance of the material, improves the voltage platform, specific capacity and electrochemical performance, allowing the iron-based phosphate composite material to exhibit excellent electrochemical performance.
Smart Images

Figure CN117727924B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and more specifically, to a dual-site doped iron-based phosphate composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the global economy, energy crisis and environmental pollution problems are becoming increasingly serious. The development and utilization of clean energy such as solar energy, wind energy, and ocean tidal energy has become an inevitable trend. As the most efficient energy storage technology, secondary batteries are a strong support for clean energy technology, and their research and development are of great significance. Lithium-ion batteries have high energy density and long cycle life. They are not only widely used in portable electronics, but also have developed rapidly in recent years as the preferred power source for electric vehicles and energy storage power stations. With the continuous expansion of global large-scale energy storage demand, the shortage of lithium resources on the earth will become a bottleneck restricting the large-scale application of lithium-ion batteries in the future.
[0003] Sodium-ion batteries are widely considered to be an effective alternative or supplement to lithium-ion batteries due to their abundant sodium resources, low price, and similar working principles to lithium-ion batteries. Developing low-cost, high-performance cathode materials is one of the keys to promoting the industrialization of sodium-ion batteries. x Fe x-1 (PO4) x-2 (P2O7), x = 3 or 4) is one of the ideal choices for positive electrode materials of sodium ion batteries due to its low cost, good structural stability and long cycle life. However, due to its low inherent electronic conductivity, low operating voltage and unstable crystal structure, it is modified by means such as carbon coating. However, the current synthesis of carbon-coated sodium iron phosphate, although it solves the problem of low material conductivity and improves the stability of the crystal structure to a certain extent. But it still affects the performance of the material's rate performance and cycle stability, hindering its electrochemical performance and practical application. Summary of the invention
[0004] Based on the above technical problems existing in the prior art, the present invention provides a dual-site doped iron-based phosphate composite material, which can effectively improve the rate performance and cycle stability of sodium iron pyrophosphate by doping specific elements at the sodium site and the iron site, so that the iron-based phosphate composite material exhibits excellent electrochemical properties.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] A dual-site doped iron-based phosphate composite material, the composite material comprising a core body and a coating layer, the molecular formula of the core body is: Na 4-n B n Fe 3-m A m(PO4)2P2O7; wherein, A and B satisfy the following relationship: d = m / 2 + n, where 0 < m < 0.3, 0 < n < 0.3, 0 < d < 0.3; A is at least one of Zr, Cu, Mg, Sn, Mn, Co; B is at least one of Li, K; the coating layer is a carbon coating layer.
[0007] In some embodiments, 0.15 ≤ d ≤ 0.25; 0.1 ≤ m ≤ 0.2; 0.05 ≤ n ≤ 0.1.
[0008] The present invention also provides a method for preparing the iron-based phosphate composite material of any one of the above embodiments, the method comprising the following steps:
[0009] Mix a sodium source, an iron source, a phosphorus source, a carbon source and a doping element source, dry, granulate, and calcine at 500 - 600 °C in an inert gas atmosphere or a weakly reducing gas atmosphere to obtain the iron-based phosphate composite material.
[0010] In some embodiments, the molar ratio of Na, Fe, and P in the sodium source, the iron source, and the phosphorus source is (4 - 4.03):3:3.9 - 4.03.
[0011] In some embodiments, the sodium source includes at least one of disodium dihydrogen pyrophosphate, trisodium hydrogen pyrophosphate, sodium pyrophosphate, sodium carbonate, sodium alginate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium nitrate, sodium citrate, sodium hydroxide, sodium acetate.
[0012] In some embodiments, the iron source includes at least one of ferrous chloride, ferrous oxalate, ferrous sulfate, ammonium ferrous sulfate.
[0013] In some embodiments, the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, pyrophosphoric acid, sodium pyrophosphate.
[0014] The doping element source is a compound of element A and element B, wherein the compound of element A includes but is not limited to oxides, chlorides, sulfates, nitrates, oxalates, acetates, etc. of A; the compound of element B includes but is not limited to oxides, chlorides, nitrates, sulfates, oxalates, acetates, etc. of B.
[0015] In some embodiments, the carbon source includes at least one of citric acid, glucose, sucrose, cyclodextrin, ascorbic acid.
[0016] In some embodiments, the mixing includes ball milling and / or sand milling; the material-ball ratio is 1:10-20; and the ball milling rate is 600-800 r / min. Through a specific mixing method, the energy generated by ball milling or sand milling during the mixing process can be used to break the reaction particles, and at the same time, the particles are activated by physical collision, so that a pure phase target product is obtained during the calcination process.
[0017] In some embodiments, the drying is one of freeze drying, spray drying, and vacuum drying.
[0018] In some embodiments, the heating rate is 1-3°C / min.
[0019] In some embodiments, the calcination time is 6-8 hours.
[0020] The present invention also provides a positive electrode material, which comprises any of the above-mentioned iron-phosphate composite materials or the iron-based phosphate composite materials prepared by any of the above-mentioned methods.
[0021] The present invention also provides a positive electrode, comprising the positive electrode material mentioned above.
[0022] The present invention also provides an electrochemical energy storage device, comprising the above-mentioned positive electrode.
[0023] Specifically, the electrochemical energy storage device includes but is not limited to a sodium ion battery, a sodium ion capacitor, and the like.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The dual-site doped iron-based phosphate composite material provided by the present invention can stabilize the phase change process of the iron-phosphate composite material by doping the sodium site and the iron site on the sodium iron pyrophosphate with specific elements, effectively improve the compaction density of the material, thereby improving the structural stability and cycle performance of the material, and at the same time improving the voltage platform, specific capacity and electrochemical performance of the material.
[0026] The preparation method provided by the present invention can achieve simultaneous doping and carbon coating of different sites of the iron-based phosphate material in one step, and can produce an iron-based phosphate composite material with high crystal purity and good phase stability, so that the obtained composite material has excellent electrochemical properties.
[0027] The dual-site doped iron-based phosphate composite material provided by the present invention is used as a positive electrode active material for a sodium ion battery, has a higher voltage platform and a higher specific capacity, and has a stable phase change process, excellent cycle performance, and good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is a SEM image of the iron-based phosphate composite material obtained in Example 1 of the present invention;
[0029] Figure 2 This is a SEM image of the iron-based phosphate composite material obtained in Comparative Example 1;
[0030] Figure 3 is the XRD pattern of the iron-based phosphate composite material obtained in Example 1;
[0031] Figure 4 is the XRD pattern of the iron-based phosphate composite material obtained in Comparative Example 1;
[0032] Figure 5 is the discharge specific capacity of the iron-based phosphate composite material obtained in Example 1 at a current density of 0.01C;
[0033] Figure 6 The discharge specific capacity of the iron-based phosphate composite material obtained in Comparative Example 1 at a current density of 0.01C;
[0034] Figure 7 This is a cycle curve diagram of the iron-based phosphate composite material obtained in Example 1 when cycled at a current density of 0.5C. DETAILED DESCRIPTION
[0035] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0037] Example 1
[0038] A dual-site doped iron-based phosphate composite Na 3.9 Li 0.1 Fe 2.85 Mn 0.15 The preparation method of (PO4)2P2O7 / C comprises the following steps:
[0039] 0.041 mol of sodium acetate, 0.04 mol of ammonium dihydrogen phosphate, 0.03 mol of ferrous oxalate, 0.001 mol of lithium acetate, 0.0015 mol of manganese sulfate and 0.04 mol of citric acid were mixed and added to a ball mill, and a small amount of ethanol was added (to make the mixed raw materials completely wet), the material-ball ratio was 1:20, and then the ball milling was carried out at a ball milling speed of 600 r / min for 2 hours; after the ball milling was completed, vacuum drying and granulation were carried out to obtain a precursor;
[0040] The precursor was heated to 600°C at a heating rate of 2°C / min in an argon gas atmosphere and calcined at 600°C for 8 hours. After the calcination, the precursor was cooled to room temperature in the furnace to obtain an iron-based phosphate composite material.
[0041] The obtained iron-based phosphate composite material was characterized. The characterization results are as follows Figure 1 and Figure 3 shown.
[0042] Figure 1 The SEM image of the composite material obtained in this embodiment is Figure 1 It can be seen that the composite material obtained in this application has relatively uniform spherical particles and a relatively smooth surface. After testing, the tap density of the composite material obtained in this embodiment is 0.944 g / cm 3 .
[0043] The composite material obtained in this example was subjected to electrochemical performance testing. The test results are as follows: Figure 5 and Figure 7 shown.
[0044] like Figure 5 The composite material obtained in this embodiment has a discharge specific capacity of 117.26 mAh / g at a voltage of 1.7-4.3 V and a current density of 0.01 C;
[0045] like Figure 7 The composite material obtained in this embodiment has a discharge capacity retention rate of 95.7% after 100 cycles at a voltage of 1.7-4.3V and a current density of 0.5C.
[0046] Example 2
[0047] A dual-site doped iron-based phosphate composite Na 3.9 K 0.1 Fe 2.85 Mn 0.15 The preparation method of (PO4)2P2O7 / C comprises the following steps:
[0048] 0.041 mol of sodium acetate, 0.04 mol of ammonium dihydrogen phosphate, 0.03 mol of ferrous oxalate, 0.001 mol of potassium chloride, 0.0015 mol of manganese sulfate and 0.04 mol of citric acid were mixed and added to a ball mill, and a small amount of ethanol was added (to make the mixed raw materials completely wet), the material-to-ball ratio was 1:20, and then the ball milling was carried out at a ball milling speed of 600 r / min for 2 hours; after the ball milling was completed, vacuum drying and granulation were carried out to obtain a precursor;
[0049] The precursor was heated to 600°C at a heating rate of 2°C / min in an argon gas atmosphere and calcined at 600°C for 8 hours. After the calcination, the precursor was cooled to room temperature in the furnace to obtain an iron-based phosphate composite material.
[0050] After testing, the composite material obtained in this embodiment has a core chemical formula of Na 3.9 K 0.1 Fe 2.85 Mn 0.15 (PO4)2P2O7. The tap density of the composite material is 0.927g / cm 3 .
[0051] After testing, the composite material obtained in this embodiment has a discharge capacity of 116.15 mAh / g at a voltage of 1.7-4.3 V and a current density of 0.01 C; and a discharge capacity retention rate of 96.4% after 100 cycles at a voltage of 1.7-4.3 V and a current density of 0.5 C.
[0052] Example 3
[0053] A dual-site doped iron-based phosphate composite Na 3.9 Li 0.1 Fe 2.85 Mn 0.15 The preparation method of (PO4)2P2O7 / C comprises the following steps:
[0054] 0.041 mol of sodium acetate, 0.04 mol of ammonium dihydrogen phosphate, 0.03 mol of ferrous oxalate, 0.001 mol of lithium acetate, 0.0015 mol of manganese sulfate and 0.04 mol of citric acid were mixed and added to a ball mill, and a small amount of ethanol was added (to make the mixed raw materials completely wet), the material-to-ball ratio was 1:15, and then the ball milling was carried out at a ball milling speed of 800 r / min for 2 hours; after the ball milling was completed, vacuum drying and granulation were carried out to obtain a precursor;
[0055] The precursor was heated to 550°C in an argon gas atmosphere at a heating rate of 2°C / min and calcined at 550°C for 8 hours. After the calcination, the precursor was cooled to room temperature in the furnace to obtain an iron-based phosphate composite material.
[0056] After testing, the composite material obtained in this embodiment has a core chemical formula of Na 3.9 Li 0.1 Fe 2.85 Mn 0.15 (PO4)2P2O7. The tap density of the composite material is 0.938g / cm 3 .
[0057] After testing, the composite material obtained in this embodiment has a discharge capacity of 116.76 mAh / g at a voltage of 1.7-4.3 V and a current density of 0.01 C; and a discharge capacity retention rate of 95.5% after 100 cycles at a voltage of 1.7-4.3 V and a current density of 0.5 C.
[0058] Example 4
[0059] A dual-site doped iron-based phosphate composite Na 3.9 Li 0.1 Fe 2.85 Mg 0.15 The preparation method of (PO4)2P2O7 / C comprises the following steps:
[0060] 0.041 mol of sodium acetate, 0.04 mol of ammonium dihydrogen phosphate, 0.03 mol of ferrous oxalate, 0.001 mol of lithium acetate, 0.0015 mol of magnesium chloride and 0.04 mol of citric acid were mixed and added to a ball mill, and a small amount of ethanol was added (to make the mixed raw materials completely wet), the material-ball ratio was 1:20, and then the ball milling was carried out at a ball milling speed of 600 r / min for 2 hours; after the ball milling was completed, vacuum drying and granulation were carried out to obtain a precursor;
[0061] The precursor was heated to 600°C at a heating rate of 2°C / min in an argon gas atmosphere and calcined at 600°C for 8 hours. After the calcination, the precursor was cooled to room temperature in the furnace to obtain an iron-based phosphate composite material.
[0062] After testing, the composite material obtained in this embodiment has a core chemical formula of Na 3.9 K 0.1 Fe 2.85 Mg 0.15 (PO4)2P2O7. The tap density of the composite material is 0.938g / cm 3 .
[0063] After testing, the composite material obtained in this embodiment has a discharge capacity of 117.05 mAh / g at a voltage of 1.7-4.3 V and a current density of 0.01 C; and a discharge capacity retention rate of 95.4% after 100 cycles at a voltage of 1.7-4.3 V and a current density of 0.5 C.
[0064] Example 5
[0065] A dual-site doped iron-based phosphate composite Na 3.95 Li 0.05 Fe 2.85 Mn 0.15 The preparation method of (PO4)2P2O7 / C comprises the following steps:
[0066] 0.041 mol sodium acetate, 0.04 mol ammonium dihydrogen phosphate, 0.03 mol ferrous oxalate, 0.0005 mol lithium acetate, 0.0015 mol manganese sulfate and 0.04 mol citric acid were mixed and added to a ball mill, and a small amount of ethanol was added (to make the mixed raw materials completely wet), the material-ball ratio was 1:20, and then the ball milling was carried out at a ball milling speed of 600 r / min for 2 hours; after the ball milling was completed, vacuum drying and granulation were carried out to obtain a precursor;
[0067] The precursor was heated to 600°C at a heating rate of 2°C / min in an argon gas atmosphere and calcined at 600°C for 7 hours. After the calcination, the precursor was cooled to room temperature in the furnace to obtain an iron-based phosphate composite material.
[0068] After testing, the composite material obtained in this embodiment has a tap density of 0.921 g / cm 3 .
[0069] After testing, the composite material obtained in this embodiment has a discharge capacity of 116.21 mAh / g at a voltage of 1.7-4.3 V and a current density of 0.01 C; and a discharge capacity retention rate of 95.1% after 100 cycles at a voltage of 1.7-4.3 V and a current density of 0.5 C.
[0070] Comparative Example 1
[0071] A method for preparing an iron-based phosphate composite material Na4Fe3(PO4)2P2O7 / C comprises the following steps:
[0072] 0.041 mol of sodium acetate, 0.04 mol of ammonium dihydrogen phosphate, 0.03 mol of ferrous oxalate and 0.04 mol of citric acid were mixed and added to a ball mill, and a small amount of ethanol was added (to make the mixed raw materials completely wet), the material-ball ratio was 1:20, and then the ball milling was carried out at a ball milling speed of 600 r / min for 2 hours; after the ball milling was completed, vacuum drying and granulation were carried out to obtain a precursor;
[0073] The precursor was heated to 600°C at a heating rate of 2°C / min in an argon gas atmosphere and calcined at 600°C for 8 hours. After the calcination, the precursor was cooled to room temperature in the furnace to obtain an iron-based phosphate composite material.
[0074] The obtained iron-based phosphate composite material was characterized. The characterization results are as follows Figure 2 and Figure 4 shown.
[0075] Figure 2 The SEM image of the composite material obtained in this comparative example is Figure 2 It can be seen that the composite material obtained in this comparative example has uneven particle shape, rough particle surface and many pores. After testing, the tap density of the composite material obtained in this example is 0.603 g / cm 3 .
[0076] The composite material obtained in this example was subjected to electrochemical performance testing. The test results are as follows: Figure 6 shown.
[0077] like Figure 6 The composite material obtained in this comparative example has a discharge specific capacity of 97.57 mAh / g at a voltage of 1.7-4.3 V and a current density of 0.01 C;
[0078] After testing, the composite material obtained in this comparative example has a discharge capacity retention rate of 76.47% after 100 cycles at a voltage of 1.7-4.3V and a current density of 0.5C.
[0079] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A dual-site doped iron-based phosphate composite material, characterized in that: The composite material comprises a core body and a coating layer, and the molecular formula of the core body is: Na 4-n B n Fe 3-m A m (PO4)2P2O7; wherein A and B satisfy the following relationship: d=m / 2+n, wherein 0.15≤d≤0.25; 0.1≤m≤0.2; 0.05≤n≤0.1; A is at least one of Zr, Cu, Mg, Sn, Mn, and Co; B is at least one of Li and K; the coating layer is a carbon coating layer; The preparation method comprises the following steps: The sodium source, the iron source, the phosphorus source, the carbon source and the doping element source are mixed, dried, granulated, and calcined at 500-600° C. in an inert gas atmosphere or a weak reducing gas atmosphere to obtain the iron-based phosphate composite material; The molar ratio of Na, Fe and P in the sodium source, iron source and phosphorus source is (4-4.03):3:3.9-4.03; The iron source is at least one of ferrous chloride, ferrous oxalate, ferrous sulfate and ammonium ferrous sulfate.
2. The method for preparing the dual-site doped iron-based phosphate composite material according to claim 1, characterized in that: The following steps are involved: The sodium source, the iron source, the phosphorus source, the carbon source and the doping element source are mixed, dried, granulated, and calcined at 500-600° C. in an inert gas atmosphere or a weak reducing gas atmosphere to obtain the iron-based phosphate composite material; The molar ratio of Na, Fe and P in the sodium source, iron source and phosphorus source is (4-4.03):3:3.9-4.03; The iron source includes at least one of ferrous chloride, ferrous oxalate, ferrous sulfate, and ammonium ferrous sulfate.
3. The method for preparing the dual-site doped iron-based phosphate composite material according to claim 2, characterized in that: The sodium source includes at least one of disodium dihydrogen pyrophosphate, trisodium monohydrogen pyrophosphate, sodium pyrophosphate, sodium carbonate, sodium alginate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium nitrate, sodium citrate, sodium hydroxide, and sodium acetate; and / or, the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, pyrophosphoric acid, and sodium pyrophosphate; and / or, the carbon source includes at least one of citric acid, glucose, sucrose, cyclodextrin, and ascorbic acid.
4. The method for preparing the dual-site doped iron-based phosphate composite material according to claim 2, characterized in that: The heating rate is 1-3°C / min; and / or the calcination time is 6-8h.
5. The method for preparing the dual-site doped iron-phosphate composite material according to claim 2, characterized in that: The mixing includes ball milling and / or sand milling; the material-ball ratio is 1:10-20; and the ball milling speed is 600-800r / min.
6. A positive electrode material, characterized in that The invention comprises the iron-based phosphate composite material according to claim 1 or the iron-based phosphate composite material obtained by the preparation method according to any one of claims 2 to 5.
7. A positive electrode, characterized in that Comprising the positive electrode material as claimed in claim 6.
8. An electrochemical energy storage device, characterized in that Comprising the positive electrode as claimed in claim 7.
Citation Information
Patent Citations
Doped modified ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN116682946A
Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof, positive electrode plate and sodium battery
CN116914117A